Creating an Agile enterprise - Humble, Jez; Molesky, Joanne; O'Reilly, Barry (Business consultant) (Lesson (O'Reilly Media), 2018)
Implementing an enterprise-level continuous improvement process is a prerequisite for any ongoing large-scale transformation effort (such as adopting an agile approach to software delivery) at scale. True continuous improvement never ends because, as our organization and environment evolve, we find that what works for us today will not be effective when conditions change. High-performance organizations are constantly evolving to adapt to their environment.